The definition and timing of anticipatory action to tackle food crises in East Africa: do they matter? - Jameel Observatory for Food Security Early Action (University of Edinburgh Global Academy of Agriculture and Food Security, 2023)
Summary of a virtual mini dialogues on priority topics related to the Observatory vision: vulnerable pastoral and agro-pastoral communities in target regions of East Africa are more prepared for and resilient to the effects of evolving environmental shocks and stresses on their food security and nutrition. The aim was to identify priority research, learning and other actions that the Observatory and a wider community of collaborators can tackle.
Keywords: climate change; drylands; anticipatory action; early action